2021
DOI: 10.3390/medicina57030282
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis with Nasal Polyps: Age and Disease Severity Differences in the Levels of Inflammatory Markers

Abstract: Background and objectives: The aim of our study was to analyze the concentrations of inflammatory markers in the nasal tissue of patients with chronic rhinosinusitis with nasal polyps (CRSwNPs) and controls of different age groups, as well as to find associations between age, inflammation development, and NPs. Materials and methods: Patients were divided into two groups—patients with CRSwNPs and control subjects who had nasal surgery for another reason beside CRS. Our analysis was performed across three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In addition, age may further contribute to this inconsistency. Although we selected adult patients to minish age-related interference, there may be altered immune response and different distributions of inflammatory mediators in further classifications of adults ( 51 54 ). Given that the ICOS-ICOSL signal can strengthen CD40-CD40L interaction, thus providing a co-stimulatory signal for B-cell activation ( 34 , 35 ), as well as the allergic characteristics of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, age may further contribute to this inconsistency. Although we selected adult patients to minish age-related interference, there may be altered immune response and different distributions of inflammatory mediators in further classifications of adults ( 51 54 ). Given that the ICOS-ICOSL signal can strengthen CD40-CD40L interaction, thus providing a co-stimulatory signal for B-cell activation ( 34 , 35 ), as well as the allergic characteristics of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies have shown that the levels of IL‐22 and its receptor (IL‐22R1) in invasive inflammatory cells and epithelial cells of the nasal passages of patients with CRSwNP are significantly increased. IL‐22 levels are also closely related to the severity of clinical symptoms and difficulty of treating CRSwNP 19,122–124 . IL‐22 can enhance the expression of MUC1 (a membrane‐bound mucin located on the nasal mucosa) in nasal polyp tissues via an IL‐22R1 dependent pathway (Figure 3).…”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
“…According to a factor analysis based on principal component analysis, IL-22 level positively correlated with type 2 cytokine levels and the Lund-Mackay CT score, which is a degree of sinus opacification ranges from 0 to 24 ( 39 ). Whereas another study compared the levels of cytokines across three different age groups and found significantly higher level of IL-22 in the mucosa from CRSwNP than in the control group across all age groups and correlated with the severity of clinical symptoms ( 40 ).…”
Section: Differential Expression Of Il-10 Family Cytokines In Individ...mentioning
confidence: 99%